The Idea of a University in the Context of Nepal (Sudurpaschim Spectrum, 2024)
This paper aims to discuss the conceptual aspect of university, university education, and the challenges of university education in Nepal. Governments around the world view universities and other higher education institutions as essential to achieving a number of national agendas. Investments in higher education institutions are increasing continuously with the belief that universities can be the source of continuous ideas to develop a knowledge-based economy. The idea of a university has been changing over time due to globalization and the shift in the knowledge-based economy. Education is becoming more globally integrated as new models for higher education are developed. The system of modern university education is undergoing serious transformations. In this regard, this paper has a special focus on what the prospects for University education are; in what context Nepalese university education exists; and what issues have impeded Nepal’s university education system. This discussion is qualitative in nature and is based upon relevant literature review.